Tyrosinase inhibition by a rare neolignan: Inhibition kinetics and mechanistic insights through in vitro and in silico studies. (October 2018) - Şöhretoğlu, Didem; Sari, Suat; Barut, Burak; Özel, Arzu
Graphical abstract: Highlights: 1 is as potent an inhibitor as the positive control, kojic acid against tyrosinase. It inhibited tyrosinase in an uncompetitive manner. Its inhibitory effects on α-glucosidase, AChE/BuChE were limited. Abstract: Neolignans are a large group of polyphenols found in plants and exhibit a wide range of bioactivities including cytotoxicity, apoptosis inducer, antimalarial and antifungal effects, acetylcholinesterase, tyrosinase, and α-glucosidase inhibition. In this study we tested acetylcholinesterase (AChE), butyrylcholinesterase (BuChE), tyrosinase, and α-glucosidase inhibitory effects of a rare neolignan, (-)-4- O -methyldehydrodiconiferyl alcohol 9'- O - β -glucopyranoside (1 ) in search for its new pharmaceutical effects. This compound exhibited good tyrosinase inhibition with an IC50 value of 44.62 ± 3.99 μg/mL. Enzyme kinetics and molecular modelling studies were performed to provide insights into its tyrosinase inhibition mechanism.